(untitled) (Journal of Dhaka Medical College, 2024)
Introduction: Osteoarthritis (OA) is a degenerative joint disease estimated to be the fourth leading cause of disability. Methodology: We conducted a cross-sectional observational study at BSMMU, Dhaka, from April 2018 to March 2019. Our goal was to evaluate the quality of life in knee OA patients in Bangladesh using Short Form-36 (SF-36) Health Survey and Western Ontario and McMaster Universities Osteoarthritis (WOMAC) Index. We collected data through face-to-face interviews, adhering to specific inclusion and exclusion criteria. Results: Most participants were within the 40-59 year age group, with 65.2% of patients reporting a disease duration of 1-5 years. The mean WOMAC scores differed significantly by age (p=0.001), with older patients having higher scores. Gender and monthly income did not significantly impact WOMAC scores (p>0.05). Educational status showed potential significance (p=0.074), but it did not reach statistical significance. There was a strong statistical association between total WOMAC scores and patient age (p=0.001). However, other socio-demographic factors showed no significant differences (p>0.05). Patients with shorter OA knee durations (less than one year) had notably lower WOMAC scores than those with longer durations (1-5 years), with a significant difference (F=16.513, p<0.001). In terms of OA knee grading, patients with more severe OA (grade III) had significantly higher WOMAC scores than those with less severe OA (grade I or II) (F=190.077, p<0.001). Gender, educational status, and monthly income significantly influenced SF-36 scores in knee OA patients. Male patients and those with higher educational levels reported higher SF-36 scores. Monthly income also had a significant effect (F=6.101, p=0.004), with higher income linked to higher SF-36 scores. Age did not significantly impact SF-36 scores (F=0.492, p=0.614). Body mass index (BMI) did not significantly affect health-related quality of life in OA knee patients. The elderly with more advanced and prolonged disease had lower quality of life according to WOMAC. Conclusion: It can be concluded that patients with OA knee had relatively poor quality of life in physical health component than that of mental health component and role physical domain was mostly affected among all domains. J Dhaka Med Coll. 2022; 31(2) : 201-209